Impact of climate change on agricultural insurance - Noah Gbenga Alli (Revista Activos)
Climate change poses significant challenges to agricultural systems, particularly in vulnerable regions like Nigeria, where farming serves as a primary livelihood and economic driver. This study investigates the impact of climate change on agricultural insurance by examining how temperature variability, changes in rainfall patterns, and extreme weather events influence crop yield losses, farmers’ claim filing behavior, and premium adjustments. Employing a quantitative research design with a cross-sectional survey approach, data were collected from 300 farmers and 84 insurance professionals using a structured questionnaire. The analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess relationships among latent variables, ensuring reliability and validity through Cronbach’s Alpha, Composite Reliability, Average Variance Extracted, and the Heterotrait-Monotrait Ratio (HTMT). Results revealed significant effects of climate factors on agricultural risks: changes in rainfall patterns (β = 0.673, p < 0.05) exhibited the strongest influence on crop yield losses, followed by extreme weather events (β = 0.568, p < 0.05) and temperature variability (β = 0.412, p < 0.05). Farmers’ claim filing behavior was positively correlated with claim frequency (β = 0.721, p < 0.05) and severity (β = 0.694, p < 0.05), which in turn significantly affected premium adjustments (β = 0.635, p < 0.05). The model demonstrated strong explanatory power, with R² values of 0.64 for crop yield losses and 0.58 for premium adjustments, supported by acceptable fit indices such as SRMR = 0.062 and negative Bayesian Information Criterion (BIC) values across constructs. These findings underscore the critical role of agricultural insurance in mitigating climate-induced risks and highlight the need for innovative products to enhance equity and accessibility in agricultural insurance.